The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/731657
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious Effects of Increased Intra-Abdominal Pressure on Kidney Function

Abstract: Elevated intra-abdominal pressure (IAP) occurs in many clinical settings, including sepsis, severe acute pancreatitis, acute decompensated heart failure, hepatorenal syndrome, resuscitation with large volume, mechanical ventilation with high intrathoracic pressure, major burns, and acidosis. Although increased IAP affects several vital organs, the kidney is very susceptible to the adverse effects of elevated IAP. Kidney dysfunction is among the earliest physiological consequences of increased IAP. In the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 102 publications
0
10
0
Order By: Relevance
“…acute IAP increase has adverse effects on the cardiovascular system, reduces the cardiac output and venous return and blood ow to the mesenteric vein, stimulates the renin-angiotensin system, and consequently, contraction of the arterioles and renal vein, reduction of renal blood ow, and increase of the hydrostatic pressure of the Bowman's capsule that, in turn, reduces the glomerular ltration rate and decreases the urine volume. According to various studies, an inverse correlation has been found between higher IAP and urine volume (13,16).…”
Section: Discussionmentioning
confidence: 98%
“…acute IAP increase has adverse effects on the cardiovascular system, reduces the cardiac output and venous return and blood ow to the mesenteric vein, stimulates the renin-angiotensin system, and consequently, contraction of the arterioles and renal vein, reduction of renal blood ow, and increase of the hydrostatic pressure of the Bowman's capsule that, in turn, reduces the glomerular ltration rate and decreases the urine volume. According to various studies, an inverse correlation has been found between higher IAP and urine volume (13,16).…”
Section: Discussionmentioning
confidence: 98%
“…Increase in IAP is known to affect the renal function adversely. [ 4 10 11 12 ] Demarchi et al recently noted IAP values of >8 mmHg to predict the development of AKI. [ 13 ] Contrastingly, we noted a lack of effect of IAP on early AKI when evaluating the relationship in critically ill obstetric patients.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] It is documented that not only IAH but even moderate rise in IAP of 8 mmHg or greater can be associated with deterioration in renal functions. [ 4 ] To diagnose an acute deterioration in renal function serum creatinine and/or urine output are conventionally relied on and be nonspecific as well. However, both these parameters are known to change late in the course of renal insult.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary nitric oxide metabolites are increased in compensated, but not in decompensated, chronic heart failure induced by establishing an artificial aorto-caval fistula in rats, implicating that this mechanism becomes exhausted with advancing heart failure [ 118 , 119 ]. Regrettably, the anatomical relationship between the aorto-caval fistula and renal vessels (whether infra- or suprarenal) was not communicated in the latter publications [ 118 , 119 ]. The deterioration of RPF was less pronounced in the compensated heart failure group than in the control group at 10 and 14 mmHg.…”
Section: Humoral Factorsmentioning
confidence: 99%
“…The administration of a nitric oxide synthase inhibitor eliminated the beneficial effect and RPF became worse than in the control group with attenuated parallel changes in GFR [ 118 , 119 ]. Hyper-perfusion and a proportionally (about 60%) increased GFR were observed in the control group after the termination of insufflation.…”
Section: Humoral Factorsmentioning
confidence: 99%